2020
DOI: 10.1038/s41598-020-75633-1
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-oxide and the reverse cholesterol transport in cardiovascular disease: a cross-sectional study

Abstract: The early atherosclerotic lesions develop by the accumulation of arterial foam cells derived mainly from cholesterol-loaded macrophages. Therefore, cholesterol and cholesteryl ester transfer protein (CETP) have been considered as causative in atherosclerosis. Moreover, recent studies indicate the role of trimethylamine N-oxide (TMAO) in development of cardiovascular disease (CVD). The current study aimed to investigate the association between TMAO and CETP polymorphisms (rs12720922 and rs247616), previously id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 58 publications
3
24
1
Order By: Relevance
“…This finding suggests that a reduction of mitochondrial function might occur in individuals that display lower TMA. This is in accordance with our previously published data describing a subtle but significant reduction of TMA in CAD patients with respect to controls, while no significant differences were measured for TMAO between the two groups (Bordoni et al, 2020b).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding suggests that a reduction of mitochondrial function might occur in individuals that display lower TMA. This is in accordance with our previously published data describing a subtle but significant reduction of TMA in CAD patients with respect to controls, while no significant differences were measured for TMAO between the two groups (Bordoni et al, 2020b).…”
Section: Discussionsupporting
confidence: 93%
“…An increased BMI was also measured in CAD patients with respect to controls (controls: 27.8±4.1; CAD: 28.8±4.5; F=5.18; p=0.023). A detailed comparison of TMA, TMAO, BMI and GFR in the CAD population vs controls in this population has been previously published (Bordoni et al, 2020a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study plasma TMAO was negatively associated with the presence of soft plaque, total plaque burden, and calcified plaque burden in univariate and multivariable models after adjusting for age, sex, and traditional risk factors. Whilst this finding contrasts with some prior studies that have found TMAO is associated with increased incidence of major adverse cardiovascular events in patients with established CAD, peripheral artery disease or chronic kidney disease, it is in keeping with other studies that have not confirmed an association with CAD and have suggested there may be a more nuanced relationship [ 39 , 40 , 41 ]. TMAO is generated through the oxidation of trimethylamine (TMA) by TMA monooxygenase present in some gut microbiota [ 42 ].…”
Section: Discussioncontrasting
confidence: 83%
“…TMAO has been shown in animal models to up-regulate macrophage receptors associated with atherosclerosis [ 29 ]. Elevated serum concentrations of TMAO have been linked to adverse cardiovascular outcomes in humans [ 29 , 30 ] and TMAO has been identified as a cardiovascular disease risk factor and biomarker in humans [ 31 ]. TMAO is also a product of phospholipid and carnitine metabolism by the intestinal microbiome.…”
Section: Discussionmentioning
confidence: 99%